Pharmacy Students' Perceptions and Attitudes towards Online Education during COVID-19 Lockdown in Saudi Arabia - Saleh Alghamdi; Majid Ali (MDPI AG, 2021)
In March 2020, a national lockdown in Saudi Arabia due to the pandemic forced all educational institutions to complete their academic year via online education. This study aims to explore pharmacy students' perceptions and assess their attitude towards online education during the lockdown. A cross-sectional self-administered survey was designed to collect responses of pharmacy students (from one college of pharmacy in Saudi Arabia) from December 2020 through January 2021. A total of 241 students completed the survey. Students' responses indicated that they had easy access to the technology, online skills, motivation and overall favorable acceptance for online learning and examinations. There was a significant difference in the mean scores between the students from different years of study (p = 0.013) related to technology access, and the male students were in significantly more favor of online examinations than female students (p = 0.009). The majority of the students indicated that the lockdown had no or negative impact on their learning and training. Students have general acceptance for online education delivery due to more technology access and online skills. More research should explore the factors affecting and the extent of the impact of online education on student learning and training.